Diagnóstico nutricional de crianças de zero a cinco anos atendidas pela rede municipal de saúde em área urbana da região sul do Brasil, 1988 Nutritional diagnosis of children under five years of age assisted by the municipal health network an urban area in the Southern Region of Brazil, 1988 - Erica Ell; Lydia M.M. Loureiro; Silvia A. Gugelmin; Sônia M.R. Cruz (Universidade de São Paulo, 1992)
Como um dos requisitos para a operacionalização do Sistema de Vigilância Alimentar e Nutricional (SISVAN) no município de Curitiba, PR, Brasil, foi realizado um levantamento epidemiológico retrospectivo com dados de 1988, que buscou através do exame antropométrico conhecer a prevalência e as formas de desnutrição calórico-protéico de crianças menores de cinco anos atendidas pela Rede Municipal de Saúde de Curitiba. Numa amostra de 4.213 crianças encontrou-se pela Classificação de Gòmez 28,1% de desnutridos, sendo que 3,6% destes situam-se no grau II e III. A Classificação de Seoane e Latham modificada por Batista Filho revelou que 19,7% das crianças apresentam alguma forma de desnutrição. O perfil antropométrico revelou maior concentração de crianças no primeiro decil a partir do sexto mês de vida, sendo esta mais acentuada no grupo etário de 12 a 24 meses para os índices: peso/idade e altura/idade. An epidemiological survey was undertaken to fulfil one of the conditions required for the establishment of the Nutritional Surveillance System, on the basis of data from 1988. In this survey an anthropometric examination was employed for the purpose of discovering the prevalence and the kinds of protein energy malnutrition among children under five years of age who had been assisted at Health Centers of the Municipal Health Department of Curitiba, Paraná (Brazil). Of a sample population of 4,213 children it was found (by the Gòmez criterion) that 28.1% had malnutrition 3.6% of this percentage being of second or third degree. By the use of the Seoane-Latham criterion as modified by Batista Filho, 19.7% of the children presented some kind of malnutrition. The distribution of the sample in centiles showed that it contained an excess of children in the first centiles after 6 th months of age as compared with the reference population. This excess was more evident in the 12 to 24-months age group.